The impact of coaching practices on player outcomes in rugby union: A systematic review - Malkin, M.; Morgan, P.; Yan, J.; Eather, N. (Journal of Sports Sciences, 2025)
Purpose: To investigate the impact of rugby union coaching practices on athlete outcomes including performance, wellbeing and engagement.